NEW APPROACHES TO TRAINING OF ENGINEERING AND ADMINISTRATIVE PERSONNEL - A. Tikhonov; V. Stroev (Вестник университета)
Article is devoted to consideration of features of the Russian system of engineering and administrative education in which several types of competences can be combined. The main directions of development of educational processes and scientific research are analyzed, the main problems and possible ways of their decision in the field of preparation of engineering and administrative shots for the domestic industry are allocated. Recommendations are given on the formation of a program for training managerial personnel based on the country's leading universities, which include a full range of engineering and technical specialties, training areas for management, and professionals who have advanced methods of business and communication training.